P2.075 Evaluation of Female Urine and Vaginal Swabs Using the BD ProbeTec™ Trichomonas Vaginalis Q x Amplified DNA Assay on the BD Viper™ System in Extracted Mode and a Cleared NAAT TV Assay as Compared to PIS. (13th July 2013) - Taylor, S N; Smith, B; Schwebke, J; Lebed, J; Fuller, D; Lillis, R; Gaydos, C A; Pol, B Van Der; Nye, M; Body, B
Abstract : Background: Trichomonas vaginalis (TV) is a sexually transmitted organism associated with vaginitis, cervicitis, urethritis, low birth weight, preterm delivery, pelvic inflammatory disease and HIV transmission and acquisition. Nucleic acid amplification testing improves the sensitivity for detection of pathogens. The performance of the BD ProbeTec™ TV Qx (TVQ) Amplified DNA Assay and the Gen-Probe Aptima TV assay were compared to patient infected status (PIS) established by the InPouch TV culture and wet mount for the detection of trichomonas in women. Methods: Participants with symptoms of trichomonas or presenting for routine visit were enrolled from seven geographically diverse centres. First void urine, a patient collected vaginal swab, and three clinician-collected vaginal swabs were obtained from each participant. Urine was aliquoted into BD neat and UPT tubes as well as an Aptima UTT tube. The first two clinician-collected vaginal swabs were randomised for wet mount and InPouch TV culture. The third was used for the Aptima TV assay. Results: There were a total of 1034 compliant participants with evaluable PIS. Specimen and instrument level exclusions resulted in 830 compliant vaginal result sets and 733 neat, UPT and UTT urine result sets for evaluation. For vaginal specimens, the sensitivity (specificity) of the TVQ Assay and the Aptima TV Assay compared to PIS were 98.3% (99%) and 100% (98.3%), respectively. For BD neat and UPT urine specimens, the sensitivity (specificity) of the TVQ Assay compared to PIS were 95.5% (98.7%) and 94.6% (98.6%). For the Aptima UTT urine specimen, the sensitivity and specificity of the Aptima TV Assay compared to PIS were 97.3% and 98.7%. Conclusion: The BD ProbeTec™ Trichomonas vaginalis Q x Amplified DNA Assay on the BD Viper™ System in extracted mode demonstrated excellent performance characteristics that were comparable to the only commercially available nucleic acid amplification assay for the detection of Trichomonas vaginalis.